2020
DOI: 10.24059/olj.v24i1.1988
|View full text |Cite
|
Sign up to set email alerts
|

A dramaturgical perspective of online university student behaviours in a second year psychology class

Abstract: This study applies dramaturgical sociology, specifically Goffman’s approach to region behaviour, to explore where students spend their time doing class related tasks in spaces other than the LMS. The context for this research is a case study of a second year psychology class at an Australian university. Data was collected about students’ front stage setting (the LMS) and backstage setting (students’ experiences on Facebook).  Over a 12-week semester 126 students were observed in the LMS. During the semester, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Social/informal collaboration refers to student-initiated collaboration on social media platforms or in other informal ways to build social ties and learning support networks outside the formal learning environment. Gilmore (2020) discovered that strong social ties build social inclusion and create a more effective learning experience.…”
Section: Facilitation Is Key To Effective Online Collaborationmentioning
confidence: 99%
“…Social/informal collaboration refers to student-initiated collaboration on social media platforms or in other informal ways to build social ties and learning support networks outside the formal learning environment. Gilmore (2020) discovered that strong social ties build social inclusion and create a more effective learning experience.…”
Section: Facilitation Is Key To Effective Online Collaborationmentioning
confidence: 99%
“…In some other cases, tools were used which students did not even know how to use (Maz et al, 2012 ; AUTHOR). This shows that the results from some research studies which identified the crucial elements for virtual campus to succeed (greater interaction of students with the tools available on the platform) (Binyamin et al, 2019 ; Gilmore, 2020 ; Gómez & Moreno, 2018 ; Ohliati & Abbas, 2019 ; Villalón et al, 2019 ), had not been fully developed.…”
Section: Introductionmentioning
confidence: 99%